EVALUASI KUALITAS PRODUK SUSU KECAMBAH KACANG HIJAU, KAJIAN DARI UMUR KECAMBAH DAN KONSENTRASI Na-CMC - Yua Wea, Agnes Saferina; Widodo, Richardus; Pratomo, Yakobus Agus (Heuristic, 2014)
Mung bean (Phaseolus radiatus L.) is one kind of nuts that have been widely knownthroughout the community. Mung beans contain high nutrient value, so it has the potential to bedeveloped into refined products such example is a highly nutritious vegetable milk. This studyaims to determine the effect of age of sprouts and Na-CMC concentration on the quality of milkproduced mung bean sprouts. The research method using a randomized block design (RBD),which consists of two factors and factorial arranged. The first factor is the age of sprouts (K)which sprouts 12 hours, 24 hours and 36 hours. While the second factor is the concentration ofNa-CMC (N) of 0.2%, 0.3% and 0.4%. From each treatment was repeated three times. Analysisthat used to milk mung bean sprouts are the levels of protein, vitamin C, fat content, viscosity andorganoleptic test consists of aroma, flavor and color.The results showed that there was no significant interaction between the two levels of afactor. At the age of sprouts showed treatment differences were highly significant effect on levelsof protein, vitamin C and viscosity, but did not show significant differences in the effects on fatcontent. While treatment concentrations of Na-CMC manunjukkan no significant difference in theeffect of the protein content, vitamin C, fat content and viscosity, but the addition of Na-CMCconcentration can increase the viscosity of milk. Organoleptic assessment results showed that thetreatment of the aroma that gets the highest percentage was K1N1 (sprouts aged 12 hours at aconcentration of 0.2% Na-CMC), treatment K1N3 (sprouts aged 12 hours at a concentration ofNa-CMC 0.4%) received the highest percentage the flavor while for the color treatment that getsthe highest percentage was K1N3 (age sprouts 12 hours with concentrations of Na-CMC 0.4%)and K2N3 (age sprouts 24 hours with concentrations of Na-CMC 0.4%).Kata kunci: kacang hijau, susu kecambah kacang hijau, umur kecambah, kosentrasi Na-CMC